Hubungan Status Gizi Ibu Dan Pola Asuh Dengan Stunting Pada Balita Usia 24-36 Bulan Di Puskesmas Rambangaru - Antonetha Rosni Hunggumila; Kartini Pekabanda; Veronika Toru; Ester Radandima (Fakultas Ilmu Kesehatan Universitas Gresik, 2023)
Stunting describes the condition of failure to thrive in toddlers. Maternal nutritional status during pre-pregnancy, pregnancy and lactation is a critical period for child growth and development. In addition to maternal factors, parenting plays a very important role in the nutritional status of children. This study aims to determine the relationship between maternal factors and child care patterns with stunting. Research Design: The research design used a cross sectional method with a sample size of 106 children under five. Collecting data through interviews using a questionnaire with a sampling technique of systematic random sampling. The variables studied were stunting, maternal nutritional status, SEZ, Hb levels, feeding practices, hygiene habits and child care. Results: Stunting was found to be 43.4%, maternal nutritional status (BMI) was thin by 38.7%, anemia during pregnancy 25.5%, KEK 17%, poor feeding practices by 54%, poor hygiene habits 62, 3% and child caregivers who are not biological mothers 66%. Variables related to stunting were hygiene habits (AOR=3.342;95%CI=1.266-8.825;p=0.01) and KEK variables (AOR=4.293;95%CI=1.054-17.486;p=0.04). Variables that were not associated with stunting were maternal nutritional status (BMI), Hb levels, feeding practices and child care. Conclusion: Chronic energy deficiency during pregnancy and hygiene habits were found to be associated with stunting. Suggestions to increase educational activities for pregnant women about nutrition through empowering groups of MCH enthusiasts and families in an effort to improve family nutrition and clean living behavior.